TANGGAPAN PENGUNJUNG TERHADAP PELAKSANAAN SAPTA PESONA DI MUSEUM ADITYAWARMAN KOTA PADANG - Monica Sandra; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The concept of Sapta Pesona is exemplified by a tourist item made up of seven parts: clean, neat, safe, cool, beautiful, and friendly, as well as memories to make visitors feel more at ease. In Padang City, the Adityawarman Museum is a tourist attraction that uses the Sapta Pesona concept incorrectly, making visitors feel uneasy. Therefore, the goal of this study is to enhance the Sapta Pesona's use at the Adityawarman Museum in Padang City to attract more visitors. This quantitative descriptive study included a sample of 99 individuals. This study collects data through interviews and questionnaires. for the Likert scale's use in research measurement. According to the findings of the research, the Appreciation Response to the Application of Sapta Pesona at the Adityawarman Museum is rated as good with (66,2%); the orderly element is quite good (58.73%), the safe element is good (69.6%), the clean element is good (67.07%), the cool element is very good (84.84%), the beautiful element is good (75.25%), hospitality is good (63.30%), memories are quite good (59.98%). It is necessary to improve the implementation of Sapta Pesona to make the Adityawarman Museum a better historical tour. Keywords: Response , Sapta Pesona , Adityawarman Museum